PHYSICOCHEMICAL PROPERTIES OF STARCH FROM AVOCADO SEED (PERSEA AMERICANA MILL) - dos Santos, Danilo Martins; Ascheri, Diego Palmiro Ramirez; Bukzem, Andrea de Lacerda; Morais, Cleiber Cintra; Carvalho, Carlos Wanderlei Piler; Ascheri, José Luis Ramírez (Boletim do Centro de Pesquisa de Processamento de Alimentos, 2017)
The extraction and characterization of avocado starch isolated from seeds (Persea americana Mill) were studied. The starch was extracted by steeping, wet grinding and sedimentation process and calculated its yield. Isolated starch was then characterized for chemical composition, morphology and granules size distribution, X-ray diffraction an mid-infrared spectra, swelling powder and solubility, pasting and thermal properties and clarity and syneresis behavior. The starch yield was 42.2%. The results showed starch granules were predominantly ellipsoidal with an average granule size of 17.83 μm. Exhibited B-type X-ray diffraction pattern with 25.7% of crystallinity, and apparent amylose content of 21.5% with similar mid-infrared spectra to other starches. Onset and peak gelatinization temperatures were 67.6 and 76.0 °C, respectively, and gelatinization enthalpy was 14.9 J/g. Starch suspensions showed peak viscosity at 4421 cP and high retrogradation tendency, which was evidenced by opaque gels and syneresis.